DETURKIFIKASI DALAM TAFSIR HAK DINI, KUR’AN DILI KARYA ELMALILI HAMDI YAZIR - Achmad Yafik Mursyid (UIN Sunan Kalijaga Yogyakarta, 2020)
The transition from the Ottoman Empire to the Republic of Turkey left a long debate between Ulama (Islamic scholars) and the proponents of this system. This transition also affected Turkish religious life patterns with the emergence of